Understanding the Factors Influencing the Success of Housing and Settlement Information Systems: A Case Study of Rental Flats in Jakarta Using the Delone & McLean Model - Dede Haryadi; Nilo Legowo (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Jakarta's rapid urban expansion has intensified housing demand, leading the government to deploy the Housing and Settlement Information System (SIRUKIM) as a digital tool to enhance transparency and administrative efficiency in subsidized rental flat management. Despite this initiative, notable shortcomings persist in areas such as service responsiveness, openness of information, and the willingness of users to engage with the platform. Objective: This study examines the key determinants of SIRUKIM's operational success by employing an augmented version of the DeLone and McLean Information Systems Success Model, enriched with trust and perceived security as supplementary explanatory variables. Methods: A quantitative research approach was applied, collecting primary data from 396 active SIRUKIM users during April to May 2024. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS. Results: Findings reveal that service quality significantly shapes both system use and user satisfaction, whereas system quality and information quality show no meaningful impact on usage behavior. User satisfaction emerged as the strongest predictor of both system use and net benefits. Trust was found to be a critical antecedent of all three quality constructs, while perceived security did not significantly influence usage. Conclusion: The results affirm that user satisfaction and institutional trust are central to the success of government-run information systems. These insights offer practical guidance for Jakarta policymakers and the SIRUKIM development team, particularly in terms of improving service quality and cultivating trust-enhancing mechanisms to drive broader system adoption.